Long-term stable timing fluctuation correction for a picosecond laser with attosecond-level accuracy - Hongyang Li; Keyang Liu; Ye Tian; Liwei Song (High Power Laser Science and Engineering)
Rapid advancements in high-energy ultrafast lasers and free electron lasers have made it possible to obtain extreme physical conditions in the laboratory, which lays the foundation for investigating the interaction between light and matter and probing ultrafast dynamic processes. High temporal resolution is a prerequisite for realizing the value of these large-scale facilities. Here, we propose a new method that has the potential to enable the various subsystems of large scientific facilities to work together well, and the measurement accuracy and synchronization precision of timing jitter are greatly improved by combining a balanced optical cross-correlator (BOC) with near-field interferometry technology. Initially, we compressed a 0.8 ps laser pulse to 95 fs, which not only improved the measurement accuracy by 3.6 times but also increased the BOC synchronization precision from 8.3 fs root-mean-square (RMS) to 1.12 fs RMS. Subsequently, we successfully compensated the phase drift between the laser pulses to 189 as RMS by using the BOC for pre-correction and near-field interferometry technology for fine compensation. This method realizes the measurement and correction of the timing jitter of ps-level lasers with as-level accuracy, and has the potential to promote ultrafast dynamics detection and pump–probe experiments.